2011
DOI: 10.1098/rstb.2010.0398
|View full text |Cite
|
Sign up to set email alerts
|

How placebo responses are formed: a learning perspective

Abstract: Despite growing scientific interest in the placebo effect and increasing understanding of neurobiological mechanisms, theoretical conceptualization of the placebo effect remains poorly developed. Substantial mechanistic research on this phenomenon has proceeded with little guidance by any systematic theoretical paradigm. This review seeks to present a theoretical perspective on the formation of placebo responses. We focus on information processing, and argue that different kinds of learning along with individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
254
1
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 270 publications
(273 citation statements)
references
References 75 publications
10
254
1
8
Order By: Relevance
“…The placebo effect is defined as the reduction of a symptom, reported by the patient, after the administration of a placebo; it is modulated by the patient's perception of the placebo action 4 . In accordance with recent reports, there are some neurobiological and psychobiological mechanisms which are implicated in placebo effect: expectation and brain reward circuitry, and conditioning 5,6,7 . It has been proposed that positive expectation before treatment relates to positive responses to placebo, through the brain reward circuitry; thus, responsiveness to placebo would be directly related to the effectiveness of the reward system, which is variable between individuals.…”
Section: What Is Placebo Effect? What It Means In Clinical Practice?mentioning
confidence: 49%
“…The placebo effect is defined as the reduction of a symptom, reported by the patient, after the administration of a placebo; it is modulated by the patient's perception of the placebo action 4 . In accordance with recent reports, there are some neurobiological and psychobiological mechanisms which are implicated in placebo effect: expectation and brain reward circuitry, and conditioning 5,6,7 . It has been proposed that positive expectation before treatment relates to positive responses to placebo, through the brain reward circuitry; thus, responsiveness to placebo would be directly related to the effectiveness of the reward system, which is variable between individuals.…”
Section: What Is Placebo Effect? What It Means In Clinical Practice?mentioning
confidence: 49%
“…Placebo responses (PR) arise from complex and heterogeneous psychoneurobiological learning processes (1), involving contextual conditioning, expectation formation and social learning mechanisms (2). They can be elicited by the perceived treatment context consisting of a variety of interrelated implicit and explicit psychosocial as well as environmental stimulation components within the relational clinician-patient system (3).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of verbal suggestions and expectations for placebo and nocebo effects has meanwhile been demonstrated in numerous experimental studies [22,[27][28][29]. Furthermore, there is now compelling evidence for the validity of classical conditioning theory for explaining placebo effects, because drug-like effects also occur when active treatments administered repetitively are replaced with pharmacological inert interventions such as saline solutions or sugar pills [24,27,30]. Recent studies have additionally demonstrated that social observational learning represents another psychological mechanism for producing placebo responses [31].…”
Section: Introductionmentioning
confidence: 99%
“…The last contribution of the first part provided by Colloca & Miller [27] aims at interpreting, critiquing and conceptualizing the existing experimental and clinical research on placebo (and nocebo) effects though a learning perspective-the process of decoding information and creating expectations. The question whether and how human beings can activate this sort of inbuilt 'endogenous pharmacy' is of utmost interest for all areas of medicine.…”
Section: Overview Of the Theme Issuementioning
confidence: 99%
See 1 more Smart Citation